media vocationalogy mata pelajaran produk kreatif dan kewirausahaan (PKK): hasil belajar siswa SMK di kabupaten Malang - Endah Andayani; Rini Agustina; Della Rulita Nurfaizana; Imron Sya'roni (Jurnal Riset Pendidikan Ekonomi, 2023)
This study discusses the effect of implementing Vocationalology media on Creative Products and Entrepreneurship (PKK) Subjects on Learning Outcomes of Vocational High School Students in Malang Regency. The population in this study were 156 students of SMK in Malang Regency, with the sampling technique using cluster sampling. This type of research is quantitative research using experimental methods. The statistical method of this study uses t-test analysis. Based on the hypothesis test found in this study there is a significant difference in results between the implementation of Media Vocationalology in the Subject of Creative Products and Entrepreneurship (PKK) on Learning Outcomes of Vocational High School Students in Malang Regency. The results of the Paired Samples Test show the number 0.000 which is a significant difference between student learning outcomes before using Media Vocationalogy compared to after using Media Vocationalogy.